Pengembangan Sistem Informasi Manajemen Persuratan Berbasis Teknologi Information Untuk Meningkatkan Kinerja Pegawai di Kantor FITK - Putri, Dinda; Basid, Hasyim; Putra, Bintang Ridzky Dwi; Lubis, Rasyita Dewi; Darmansah, Tengku (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study focuses on the development of an information management system for correspondence based on information technology at the FITK Office to enhance employee performance. The background of this research shows that manual correspondence management hinders efficiency and productivity. The method used is a qualitative approach with secondary data analysis, including case studies and relevant literature. The aim of this research is to identify technological solutions that can improve administrative processes. The findings indicate that the application of automation technology, cloud computing, and real-time reporting features can optimize workflow, enhance data accessibility and security, and facilitate effective performance monitoring of employees. This research is expected to provide direct benefits to FITK employees and serve as a model for other educational institutions.